2016
DOI: 10.5194/npg-2016-15
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multifractal characteristic-based comparison of elements in soils within the Daxing and Yicheng areas of Hefei, Anhui Province, China

Abstract: In this paper, we study Z 2 Z 2 [u]-(1 + u)-additive constacyclic code of arbitrary length. Firstly, we study the algebraic structure of this family of codes and a set of generator polynomials for this family as a (Z 2 +uZ 2 )[x]-submodule of the ring R α,β . Secondly, we give the minimal generating sets of this family codes, and we determine the relationship of generators between the Z 2 Z 2 [u]-(1 + u)-additive constacyclic codes and its dual and give the parameters in terms of the degrees of the generator p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 177 publications
0
6
0
Order By: Relevance
“…In February 2012, the People's Congress of Guangzhou established a supervisory role over municipal obligations for the first time in history [83]. These activities brought enormous pressure on the Guangzhou government because people found that municipal debts rocketed from 115.3 billion CNY in 2008 to 247.5 billion CNY in 2010 [84] (see Table 1). Such a dramatic rise was attributed to the preparation and operation of the 2010 Asian Games [84].…”
Section: "Tor" Policy Phase 20 (2012-2015)mentioning
confidence: 99%
See 1 more Smart Citation
“…In February 2012, the People's Congress of Guangzhou established a supervisory role over municipal obligations for the first time in history [83]. These activities brought enormous pressure on the Guangzhou government because people found that municipal debts rocketed from 115.3 billion CNY in 2008 to 247.5 billion CNY in 2010 [84] (see Table 1). Such a dramatic rise was attributed to the preparation and operation of the 2010 Asian Games [84].…”
Section: "Tor" Policy Phase 20 (2012-2015)mentioning
confidence: 99%
“…These activities brought enormous pressure on the Guangzhou government because people found that municipal debts rocketed from 115.3 billion CNY in 2008 to 247.5 billion CNY in 2010 [84] (see Table 1). Such a dramatic rise was attributed to the preparation and operation of the 2010 Asian Games [84]. In December 2012, for the first time, the Guangzhou government publicly admitted the scope of debts, 241.4 billion CNY [77].…”
Section: "Tor" Policy Phase 20 (2012-2015)mentioning
confidence: 99%
“…The function relationship between the intensity of the light source and the external defects was established to achieve the detection of kiwifruit defects [5]. Li first processed the images using morphology and then used a BP neural network to categorize the external defects of kiwifruit into four classes, with an accuracy of more than 91.3% [6]. To summarize, traditional image processing techniques are available for specific recognition, but such methods have low recognition accuracy and poor stability for different samples.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between an atom and a quantized optical field (e.g. Fock states) can lead to quantum Rabi oscillation in atomic level population [1,2]. Such a Rabi oscillation between two levels can be generalized to an effect of so-called 'quantum collapse and revival' in atomic population inversion [3][4][5].…”
Section: Introductionmentioning
confidence: 99%